The Caring City : Ethics of Urban Design - Davis, Juliet (Book collections on Project MUSE., 2022)
This original study makes a compelling case for a more ethical approach to urban development and management. Countering the conventional, neoliberal thinking of urban planners and academics, it uses case studies to show how a philosophy of caring can promote the wellbeing of our cities' many inhabitants.